GLOCALIZATION INTEGRATED IN READING TEXTS OFTHE ENGLISH MODULE FOR THE SEVENTH-GRADE STUDENTS BY MGMP OF KARANGANYAR REGENCY: A CONTENT ANALYSIS - Bintang Permana Listyawati (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
This research is going to investigate how the module for teaching English to grade VII students in Karanganyar Regency embeds the principles of glocalization, which mix local elements. Glocalization is necessary in education since it cultivates sensitivity and awareness among the learners. This analysis adopts a content analysis approach to see how glocalization is reflected in the reading materials for graders. The focus of the analysis lies in aspects, cultural references, and themes, which better explain the adjustment of global English materials in contexts and cultures. The results underline the contribution of glocalization to the student's engagement and understanding during this curriculum. This research will offer insights into language teaching and the development of curriculum through the critical importance of glocalization strategies in the teaching of materials for learners to be culturally relevant. The recommendations from the conducted analysis give guidance to educators and curriculum designers to improve the implementation of glocalization principles in language teaching resources.